On Cohn's embedding of an enveloping algebra into a division ring - Wehrfritz, B.A.F. (Український математичний журнал, 1992)
In 1961 P. М. Cohn proved that the universal enveloping algebra of any Lie algebra over a field-can be embedded into a division ring. (The Lie algebra is not assumed to be finite dimensional.) Cohn's method is less than direct. We give a more explicit construction. These division rings have recently found uses in the theory of skew linear groups.